Optimizing "Open Data Jawa Tengah" through Technology Acceptance Model (TAM) - Muaafii, Yasykur Hisyam; Priyanto, Priyanto (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
The Central Java Provincial Government has implemented the "Open Data Jateng" system since 2019 for public services. Open Data is part of the application of big data, and the system does not yet have evidence to meet data needs. So, an explanatory method of research was conducted using a prediction study. The research variables are based on the development of the Technology Acceptance Model (TAM) theory and the 3Q model theory. 130 respondents from the ex-Karesidenan of Semarang City filled out 21 statements, then tested through Partial Least Square - Structural Equation Modeling (PLS-SEM). The result is that there is the highest relationship in the TAM variable, namely: the influence of the perceived usefulness variable on the behavioral intention to use variable is 42.5%, with the predictive power of increasing the two variables to 75.2% if there is treatment/policy. The relationship between TAM variables and the 3Q model was found, such as the effect between the information quality variable and perceived usefulness was 13.3%, which has a low level of influence. Although low, the predictive power is also high at 65.4% if there is a treatment or policy that supports the information quality variable. The study concluded that the optimization of Open Data Jateng can be through policy support in order to improve the quality of information.